Etika Perbankan Syari'ah - Moh Muafi Bin Thohir (Program Studi Ekonomi Islam Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Syarifuddin Lumajang, 2017)
Sharia Banking is one of the buildings of the sharia economic system that sees important ethical values, principles and norms in the operational system. As part of the economic system of Shariah that is constructed based on the concept of Islam, Shari'ah banking too, which runs on the foundation of ethical values referred to in the operationalization of Shariah banking. Benefits of this paper put ethical values contained in the texts of al-Quran and al-Sunnah is referred to as the philosophical foundation and provide input to the sharia banking community in order to act in accordance with the norms of ethics.As for the question of ethical values is the value of divinity, agency, balance, equity, and kindness. The value of divinity translated into the unity of god principle, faith,worship, morals, shariah, sanctity and absolute ownership. The value of agency come into prophethood principle, good moral, humanity, fraternity, contest, professionalism and accountability. While the equilibrium value formulated in mid principle, Islamic socialism, gratitude, speculation and involvement. The equity value translated into the principle of justice, equation and Equalization. The kindness value become maintain principles of religion, soul / mind, descendants, honor, and treasure.